The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10153362
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biomarkers in Surgery for Ulcerative Colitis: A Review

Abstract: Ulcerative colitis (UC) is an inflammatory condition that generally affects the rectum and extends proximally into the colon in a continuous, distal-to-proximal pattern. Surgical resection (total proctocolectomy) is the only cure for UC and is often necessary in managing complicated or refractory disease. However, recent advances in biologically targeted therapies have resulted in improved disease control, and surgery is required in only a fraction of cases. This ever-increasing array of options for medical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
(144 reference statements)
0
2
0
1
Order By: Relevance
“…Detailed descriptions of the clinicopathological features of ulcerative colitis have been recently published [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A gene that was highlighted in this research was CD274 ( PD-L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of the clinicopathological features of ulcerative colitis have been recently published [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A gene that was highlighted in this research was CD274 ( PD-L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of industrialization, the incidence of UC has shown a significant upward trend in the world [ 21 ]. Although studies have shown that multiple factors such as genetics, immunity, environment, and intestinal microecology may lead to the occurrence of UC, the specific mechanism of UC is still unclear [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…У пациентов с ЯК по сравнению с клинически здоровыми лицами выявлено снижение концентрации общего белка в крови на 25 %, свидетельствующее об увеличении интенсивности процессов катаболизма над анаболическими процессами, что сопровождается в ряде случаев незначительным повышением активности трансаминаз и концентрации мочевины. Данные проявления являются следствием острого воспалительного процесса, а также могут возникать при нарушениях пищевого режима и мальабсорбции, что при наличии ЯК может сопровождать заболевание, усиливая его тяжесть и снижая эффективность терапии [15].…”
Section: результаты исследованияunclassified